Cultural Experience Tourism Among the Chơ Ro People: Insights from Bà Rịa–Vũng Tàu Province, Vietnam (International Journal of Environmental Sciences, 2025)
This study aims to examine the current status and development potential of cultural experience tourism among the Chơ Ro ethnic community in Bà Rịa–Vũng Tàu Province, Vietnam, with a focus on enhancing cultural preservation and sustainable economic growth.Design/methodology/approach: A mixed-methods approach was adopted, integrating quantitative and qualitative data. The quantitative component involved a survey of 360 tourists who had participated in Chơ Ro cultural experiences, measuring satisfaction, revisit intention, and willingness to recommend. The qualitative component comprised in-depth interviews with 18 representatives from tourism businesses and restaurants offering products and services derived from Chơ Ro cultural heritage.Findings: Survey results indicate high tourist satisfaction, with 40% reporting being “very satisfied” and 35% “satisfied.” Additionally, 70% expressed an intention to revisit, and 80% were willing to recommend the experience. Notable tourism assets include traditional stilt-house architecture, indigenous survival skills, ethnic attire, weaving, folk games, performing arts, and traditional cuisine. However, infrastructure limitations, service quality gaps, and insufficient local tourism skills remain challenges.Practical implications: Recommendations include upgrading transportation infrastructure, enhancing tourism service points, training local communities in hospitality and communication, and developing innovative cultural products to diversify offerings.Originality/value:This research provides empirical evidence on the market potential of Chơ Ro experiential tourism and offers strategic directions for preserving ethnic cultural heritage while promoting sustainable tourism development in Vietnam.